"That Felt Like Real Engagement": Fostering and Maintaining Inclusive Research Collaborations With Individuals With Intellectual Disability. (January 2020) - Schwartz, Ariel E.; Kramer, Jessica M.; Cohn, Ellen S.; McDonald, Katherine E.
People with intellectual disability (ID) are increasingly involved in stakeholder-engaged research, such as "inclusive research" (IR). To understand the processes that foster and maintain IR with individuals with ID, we used a narrative interview approach with co-researchers with ID ( n = 6) and academic researchers ( n = 8). We analyzed the data using grounded theory principles. We then developed a model describing how contextual factors and team-level factors and processes coalesce to foster and maintain IR collaborations. We observed that team members' values and characteristics are foundational to IR and drive a commitment to accessibility. Contextual factors, including funding and partnership duration, influence teams' processes and structures. These processes and structures influence the extent to which co-researchers perceive the IR team to be cofacilitated or academic-facilitated. Co-researcher involvement is partially maintained by perceived personal and societal benefits. Optimizing the relationship between these factors may support involvement of people with ID in stakeholder-engaged research projects.